STUDY OF STRUCTURE AND WORKING PROCESS OF VACUUM TUBE COLLECTOR - Mamarasulov Qudratbek Shuxratbek o‘g‘li; Rahmanov Muslihiddin Muhiddin o‘g‘li (Лучшие интеллектуальные исследования, 2024)
If the vacuum solar collector is manufactured by hand, galvanized containers for water should be prepared. Its volume can be from 100 to 200 liters. The container should be placed on the roof. If the barrel is installed on the south side of the roof, 100 liters of liquid can occupy up to 60 degrees. The second should be coated with a metallic shiny layer. In this case, the efficiency coefficient is much higher, because the heat exchange area with the air is minimal. It is recommended to use such a simple solar collector in places where ecology is sufficiently preserved, it is better to operate such a system away from polluted places. It should be noted that in the winter months such units are able to produce less heat.